Endovascular Treatment of Ruptured Very Small Intracranial Aneurysms: Complications, Recurrence Rate, and Clinical Outcomes - Qin, Feiyun; Liu, Jiaqiang; Zhao, Xintong; Wu, Degang; Lai, Niansheng; Zhang, Zihuan; Li, Zhenbao (Frontiers in Neurology, 2022)
Objective: The aim of this study was to evaluate the safety and efficacy of endovascular treatment for ruptured very small (≤3 mm) intracranial aneurysms (VSIAs). Methods: The clinical data and imaging results for 152 patients with VSIAs treated with coil embolization from August 2014 to June 2020 were retrospectively reviewed. The influential factors related to the preoperative complications, aneurysm recurrence, and clinical outcomes for these patients were analyzed. Results: Among 152 patients with ruptured VSIAs, 90 were treated with coil embolization alone, while 62 were treated with stent-assisted coil embolization. Eighteen patients experienced intra and/or postoperative complications (overall incidence = 11.8%). One person died of intraoperative aneurysm re-rupture and postoperative rebleeding (mortality rate = 0.65%). Twenty patients had various degrees of neurological dysfunction (morbidity rate = 13.1%). Statistical analysis showed that there was no independent risk factor associated with perioperative complications. The rate of complete aneurysm occlusion at discharge and follow-up was 76.3 and 86.2%, respectively. A total of 105 patients underwent digital subtraction angiography during follow-up, and 18 of them experienced postoperative recurrence (recurrence rate = 17.1%). Seven patients were retreated (retreatment rate = 6.7%). The use of stents was the only factor that affected the postoperative recurrence of aneurysm. The incidence of favorable clinical outcomes (Glasgow Outcome Scale score ≥ 4) at discharge and follow-up was 86.2 and 97.1%, respectively. Univariate analysis showed that the preoperative Hunt-Hess grade, CT Fisher grade, and perioperative complications were risk factors for poor clinical outcomes. Multiple logistic regression analysis showed that perioperative complication was the most significant risk factor for the clinical prognosis of patients with ruptured VSIAs. Conclusion: Endovascular treatment is a safe and efficient approach for ruptured VSIAs. Stent-assisted coiling reduced the recurrence rate of aneurysm without increasing the incidence of perioperative complications. The Hunt-Hess grade, CT Fisher grade, and perioperative complications were independent factors associated with the clinical outcomes of patients with ruptured VSIAs, and perioperative complication was the most significant risk factor for poor prognosis in patients.